First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Do some tiger sharks prefer beaches? Insights for shark management from a broad-scale comparative tracking study - Matthew N. McMillan; Adam Barnett; Stacy L. Bierwagen; Tracey B. Scott-Holland; Vinay Udyawer; Matthew Campbell; Richard Fitzpatrick; Nicolas Lubitz; Ingo B. Miller; Leanne M. Currey-Randall (Ocean & Coastal Management, 2026)

Mapping blue carbon ecosystems from Earth observations at a national scale for Papua New Guinea - Christopher J. Owers; Richard M. Lucas; Carole Planque; Daniel Clewley; Matt Paget; Chloe Fitzpatrick; Annette Burke; Freddie Alei; Mitchell B. Lyons; Andrew D. L. Steven (Frontiers in Marine Science, 2025)
National maps are essential to support the conservation, restoration, and sustainable management of blue carbon ecosystems (BCE). This is particularly important for nations in the Indo-Pacific region, including Papua New Guinea (PNG), that aspire to integrate these ecosystems into their nationally determined contributions (NDCs) for ecosystem accounting. This study focussed on mapping the extent of BCEs in PNG using Earth observation data for the year 2020 and reporting on biomass and carbon storage services. Land cover categories were generated using the Living Earth framework for the 15 coastal provinces of PNG. The total BCE area in PNG (14,353 km²) comprised 30% mangrove, 65% lowland peat swamp forest, 3% saltmarsh, and 2% seagrass. Lowland peat swamp forests contribute the greatest biomass (137.94 ± 67.10 Tg) followed by mangroves (71.79 ± 27.16 Tg), with a total biomass of 212.99 ± 95.89 Tg. Across PNG, a total of 710.46 ± 362.75 Tg C were estimated for belowground carbon of BCEs (reporting to 1 m depth), almost seven times more than that of aboveground carbon (102.14 ± 45.97 Tg C). This study highlights the need for a consistent and standardised framework for mapping BCEs, which can support coordinated management of coastal landscapes across provinces that contribute to national policies and NDC reporting. This case study can be used as a demonstration for other nations where similar opportunities and challenges may exist for mapping BCE using Earth observations, with a framework that can be compared and adapted to user requirements.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

P07-09 Spatio-temporal multi-omics analysis of lung tissue and matched biofluids identifies circulatory safety biomarkers for monitoring inhaled drug induced lung injury - M.M. Majumder; E. Williams; M.O. Lindvall; A. Jarnuczak; G. Hamm; C. Di Poto; A.A. Iannetta; J.L. Touza; E.L. Allman; E. Miele; J. Lindgren; E. Sand; et al. (Toxicology Letters, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Developing effective management solutions for controlling stinking passionflower (Passiflora foetida) and promoting the recovery of native biodiversity in Northern Australia - Tommaso Jucker; Vicki Long; David Pozzari; Dan Pedersen; Ben Fitzpatrick; Paul B. Yeoh; Bruce L. Webber (Biological Invasions, 2020)

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Exercise training comprising of single 20-s cycle sprints does not provide a sufficient stimulus for improving maximal aerobic capacity in sedentary individuals - P. Songsorn; A. Lambeth-Mansell; J. L. Mair; M. Haggett; B. L. Fitzpatrick; J. Ruffino; A. Holliday; R. S. Metcalfe; N. B. J. Vollaard (European Journal of Applied Physiology, 2016)

Coping with aquatic hypoxia: how the plainfin midshipman (Porichthys notatus) tolerates the intertidal zone - Paul M. Craig; John L. Fitzpatrick; Patrick J. Walsh; Chris M. Wood; Grant B. McClelland (Environmental Biology of Fishes, 2014)

Clinical and mutation data in 12 patients with the clinical diagnosis of Nager syndrome - J. C. Czeschik; C. Voigt; Y. Alanay; B. Albrecht; S. Avci; D. FitzPatrick; D. R. Goudie; U. Hehr; A. J. Hoogeboom; H. Kayserili; P. O. Simsek-Kiper; L. Klein-Hitpass; et al. (Human Genetics, 2013)

Doomed before they are described? The need for conservation assessments of cryptic species complexes using an amblyopsid cavefish (Amblyopsidae: Typhlichthys) as a case study - Matthew L. Niemiller; Gary O. Graening; Dante B. Fenolio; James C. Godwin; James R. Cooley; William D. Pearson; Benjamin M. Fitzpatrick; Thomas J. Near (Biodiversity and Conservation, 2013)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Congruent population structure inferred from dispersal behaviour and intensive genetic surveys of the threatened Florida scrub‐jay ( Aphelocoma cœrulescens ) - A. COULON; J. W. FITZPATRICK; R. BOWMAN; B. M. STITH; C. A. MAKAREWICH; L. M. STENZLER; I. J. LOVETTE (Molecular Ecology, 2008)
The delimitation of populations, defined as groups of individuals linked by gene flow, is possible by the analysis of genetic markers and also by spatial models based on dispersal probabilities across a landscape. We combined these two complimentary methods to define the spatial pattern of genetic structure among remaining populations of the threatened Florida scrub‐jay, a species for which dispersal ability is unusually well‐characterized. The range‐wide population was intensively censused in the 1990s, and a metapopulation model defined population boundaries based on predicted dispersal‐mediated demographic connectivity. We subjected genotypes from more than 1000 individual jays screened at 20 microsatellite loci to two Bayesian clustering methods. We describe a consensus method for identifying common features across many replicated clustering runs. Ten genetically differentiated groups exist across the present‐day range of the Florida scrub‐jay. These groups are largely consistent with the dispersal‐defined metapopulations, which assume very limited dispersal ability. Some genetic groups comprise more than one metapopulation, likely because these genetically similar metapopulations were sundered only recently by habitat alteration. The combined reconstructions of population structure based on genetics and dispersal‐mediated demographic connectivity provide a robust depiction of the current genetic and demographic organization of this species, reflecting past and present levels of dispersal among occupied habitat patches. The differentiation of populations into 10 genetic groups adds urgency to management efforts aimed at preserving what remains of genetic variation in this dwindling species, by maintaining viable populations of all genetically differentiated and geographically isolated populations.

Evidence for size and sex‐specific dispersal in a cooperatively breeding cichlid fish - K. A. STIVER; J. K. DESJARDINS; J. L. FITZPATRICK; B. NEFF; J. S. QUINN; S. BALSHINE (Molecular Ecology, 2007)
African Great Lake cichlid populations are divided into thousands of genetic subpopulations. The low gene flow between these subpopulations is thought to result from high degrees of natal philopatry, heavy predation pressure, and a patchy distribution of preferred habitats. While predation pressure and habitat distribution are fairly straightforward to assess, data on dispersal distances and rates are scarce. In fishes, direct observations of dispersal events are unlikely, but dispersal can be studied using molecular markers. Using seven microsatellite loci, we examined dispersal in the cooperatively breeding cichlid fish, Neolamprologus pulcher . As this species is found in well‐defined groups clustered into subpopulations, we could assess dispersal on a narrow (within subpopulation) and broad (between subpopulation) scale. While fish were generally more related to others in their own subpopulation than they were to fish from other subpopulations, large males diverged from this pattern. Large males were more related to other large males from different subpopulations than they were to large males from their own subpopulation, suggesting more frequent dispersal by large males. Across subpopulations, relatedness between large males was higher than the relatedness among large females; this pattern was not detected in small males and small females. Within a subpopulation, individuals appeared to be preferentially moving away from relatives, and movement was unrestricted by the physical distance between groups. Our results highlight the importance of examining multiple spatial scales when studying individual dispersal biases.

In Vitro Earthworm Lumbricus terrestris Coelomocyte Assay for Use in Terrestrial Toxicity Identification Evaluation - S. W. Burch; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman (Bulletin of Environmental Contamination and Toxicology, 1999)

Wound Healing in Earthworms Lumbricus terrestris: A Cellular-Based Biomarker for Assessing Sublethal Chemical Toxicity - M. A. Cikutovic; L. C. Fitzpatrick; A. J. Goven; B. J. Venables; M. A. Giggleman; E. L. Cooper (Bulletin of Environmental Contamination and Toxicology, 1999)